Assessment of Work Practices and Health Problems Among Filling Station Attendants in Ile Ife - Lawal, Sodiq O.; Muhammad , Abdulafeez I.; Muili , Opeyemi A.; Ojo , Temitope O. (International Journal of Medical Students, 2023)
Background: Filling Station Attendants are exposed to hazards in their workplaces, which could be physical, chemical, ergonomic, biological, mechanical, or psychosocial. The study aimed to assess the work practices and health problems among filling station attendants in Ile-Ife. Methods: This study was conducted in Ile Ife, Osun State, Nigeria using a descriptive cross-sectional study design. There are 218 filling stations in Ile Ife. The total sampling method was used for selection and a sample size of 200 was obtained. Data was collected via Interviewer administered questionnaires with sections assessing sociodemographic characteristics, work practices, occupational hazards, and health problems using close-ended questions. An observational Checklist assessing the safety measures put in place by the management was also obtained. Data were analyzed using Statistical Package for Social Sciences (SPSS) and a p-value of 0.05 was found to be statistically significant. Results: Majority of the filling station attendants (74%) were not aware of workplace safety practices. Of those that were aware, 78% were aware of PPE while the commonest available PPE was working clothes (36%). One hundred and twelve attendants (56%) indicated that the PPEs available for them were not adequate. Concerning training, about 62.5% had prior safety training of which only 66% and 56% of them could use fire extinguishers and spill kits respectively. Regarding occupational hazards,74.5% of the attendants were aware of the various hazards, the commonest being fire outbreak (69.5). The commonest work-related problem was musculoskeletal disorders (60.5%) while the least common was gastro-intestinal tract problems (8%). There was a significant association between age, working durations of the respondents, and skin problems with p-values of 0.021 and 0.035 respectively. There was also a significant association between BMI and respiratory problems with a p-value of 0.029. Conclusion: This study assessed work practices and health problems among filling station attendants. There was poor availability of PPE, inadequate use of PPE as well as poor work safety practices among filling station attendants. Regarding health problems, neurological and eye problems were found to be the commonest among filling station attendants in Ile Ife. There were also significant associations between some sociodemographic characteristics and some health problems such as age and skin problems, working duration and skin problems, BMI, and respiratory problems.